Copper catalyst, preparation method and application thereof, and method for preparing ester and / or ketone compound by dehydrogenation of alcohol compound
The CuO and CuAl2O4 spinel phases were formed by co-precipitation method of Cu-Mn-Al-based copper catalyst, which solved the problems of high energy consumption and low catalytic activity of existing alcohol compound dehydrogenation catalysts, and achieved efficient and environmentally friendly alcohol compound dehydrogenation reaction.
Patent Information
- Application Number
- CN202411983238.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
AI Technical Summary
Existing alcohol-based dehydrogenation catalysts have potential hazards to high energy consumption, low catalytic activity, many side reactions, short lifespan and environmental and human health.
The Cu-Mn-Al-based copper catalyst was prepared by co-precipitation method, and the Cu element content was controlled at 32 wt%-60 wt%, the Mn element content was 3 wt%-16 wt%, and the Al element content was 10 wt%-32 wt%, and the CuO and CuAl2O4 spinel phases were calcined at high temperature.
The heat resistance stability and catalytic activity of the catalyst are improved, the reaction temperature and hydrogen circulation are reduced, the generation of by-products is reduced, the service life of the catalyst is extended, and the use of toxic Cr elements is avoided.
Smart Images

Figure CN119869542A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a copper catalyst, a preparation method and application thereof, and a method for preparing ester and / or ketone compounds by dehydrogenating alcohol compounds. Background Art
[0002] The preparation of esters / ketones by catalytic dehydrogenation of alcohols is a very important organic chemical reaction process, which is widely used in large-scale chemical industrial production and the production of fine chemicals. The process of direct dehydrogenation of alcohols has the advantages of mild reaction conditions, high atom economy, and environmental friendliness, showing great development potential. In addition, the direct dehydrogenation of alcohols can produce hydrogen as a by-product, which meets the requirements of sustainable energy development. In the industrial production process of catalytic dehydrogenation of alcohols, Cr-containing 6+ The use of copper metal oxides as catalysts often produces a large amount of toxic and hazardous wastes, and it is very expensive to remove these trace reagents from the reaction mixture or to recover these wastes. In addition, the current copper-based catalysts have poor low-temperature activity, low product selectivity, many side reactions, which affect subsequent separation, and a short lifespan. Therefore, how to prepare an environmentally friendly, efficient, and stable alcohol dehydrogenation catalyst is of great significance.
[0003] CN101269331A discloses a CuO-ZnO-Al2O3 sec-butyl alcohol dehydrogenation catalyst prepared by coprecipitation method, in which mesopores are prepared by adding organic active agents to increase the pore diameter and surface area to improve the activity of the catalyst. However, the pore wall of the mesoporous material is thin and the thermal stability is poor, and the catalyst structure is prone to collapse during use.
[0004] CN101757922A discloses a CuO-ZnO-Al2O3 catalyst for cyclohexanol dehydrogenation to cyclohexanone prepared by coprecipitation method, under normal pressure, reaction temperature of 230°C, feed space velocity of 0.6h -1 Under the above conditions, the conversion rate of cyclohexanol is only 48.8%, and the selectivity of cyclohexanone is 99.6%. The catalyst has low conversion rate, low cyclohexanone yield, and high reaction temperature.
[0005] CN103980241A discloses a method for producing delta-valerolactone, wherein the dehydrogenation catalyst used comprises: 15-35wt% copper, 0.2-2.0wt% silver, 1-5wt% rare earth element, 20-60wt% carrier, and the yield of delta-valerolactone exceeds 98% at a reaction temperature of 230-270°C, a reaction pressure of normal pressure -0.1MPa, and a hydrogen-alcohol molar ratio of 5-10. By adding an appropriate amount of silver to the copper-based catalyst, the activity, selectivity and service life of the catalyst are greatly improved, and the service life can be extended exponentially, but the introduction of precious metal silver also increases the production cost of the catalyst.
[0006] At present, the catalysts used for dehydrogenation of 1,4-butanediol to produce γ-butyrolactone are mainly Cu-based catalysts, including Cu-Cr-based catalysts, Cu-Zn-based catalysts, and catalysts of other systems, which have been reported in many patents.
[0007] Although the Cu-Cr catalysts have good reaction performance, the Cr element is highly toxic and can cause harm to the environment and human health. Therefore, they have been banned in Europe and North America.
[0008] In addition, CN103044367A discloses a method for synthesizing a Cu-Zn-A1 catalyst by coprecipitation, and then impregnating an alkali metal additive K or Li. At a reaction temperature of 230-250°C, a reaction pressure of 0-0.4 MPa, and a feed space velocity of 1.0-2.5 h -1 When the molar ratio of hydrogen to alcohol is 3-10, the conversion rate of 1,4-butanediol reaches 98% and the selectivity of γ-butyrolactone reaches 99%. However, under the action of this catalyst, the temperature required for the dehydrogenation reaction is high, and the catalytic activity of this catalyst needs to be improved.
[0009] Therefore, it is of great significance to develop a catalyst for dehydrogenating alcohol compounds to prepare esters and / or ketone compounds under low temperature, low hydrogen-to-alcohol ratio, and high space velocity conditions with high raw material conversion rate and high target product selectivity. Summary of the invention
[0010] The purpose of the present invention is to solve the problems in the prior art that the dehydrogenation reaction has high energy consumption and the catalytic activity needs to be improved.
[0011] In order to achieve the above object, the first aspect of the present invention provides a copper catalyst, which contains Cu element, Mn element and Al element. Based on the total weight of the copper catalyst, the content of Cu element in the copper catalyst is 32wt%-60wt%, the content of Mn element is 3wt%-16wt%, and the content of Al element is 10wt%-32wt%;
[0012] The copper catalyst contains CuO crystal phase and / or CuAl2O4 spinel phase.
[0013] A second aspect of the present invention provides a method for preparing a copper catalyst, the method comprising:
[0014] (1) Under the condition of pH value of 8-9, an aqueous solution containing copper salt, manganese salt and aluminum salt is subjected to a coprecipitation reaction at a temperature not lower than 40° C. to obtain intermediate I;
[0015] (2) subjecting the intermediate I to an aging treatment to obtain an intermediate II;
[0016] (3) calcining the intermediate II to obtain the copper catalyst.
[0017] The conditions are controlled so that the Cu content of the copper catalyst is 32wt%-60wt%, the Mn content is 3wt%-16wt%, and the Al content is 10wt%-32wt%. The copper catalyst contains CuO crystal phase and / or CuAl2O4 spinel phase.
[0018] The third aspect of the present invention provides a copper catalyst prepared by the method described in the second aspect.
[0019] The fourth aspect of the present invention provides use of the copper catalyst described in the first aspect and / or the third aspect in the dehydrogenation of alcohol compounds to prepare esters and / or ketone compounds.
[0020] A fifth aspect of the present invention provides a method for preparing ester and / or ketone compounds by dehydrogenating alcohol compounds, the method comprising: dehydrogenating the alcohol compounds in the presence of a copper catalyst to obtain ester and / or ketone compounds;
[0021] The alcohol compound is C 2-12 Monohydric alcohol or polyhydric alcohol;
[0022] The copper catalyst is the copper catalyst described in the first aspect and / or the third aspect.
[0023] Through the above technical solution, the present invention has at least the following advantages:
[0024] (1) The copper catalyst provided by the present invention does not contain Cr and will not cause harm to human health and the environment; in addition, the copper catalyst has a CuAl2O4 spinel phase, and the presence of this crystal form improves the heat stability of the catalyst, thereby improving the catalytic activity of the catalyst under high temperature conditions.
[0025] (2) When the copper catalyst provided by the present invention is used for dehydrogenation of alcohol compounds to prepare esters and / or ketone compounds, the amount of hydrogen circulation required in the reaction system is small and the reaction temperature is low, thereby reducing production energy consumption.
[0026] (3) When the copper catalyst provided by the present invention is used for dehydrogenation of alcohol compounds to prepare esters and / or ketone compounds, the catalyst has high catalytic activity and produces less by-products, which is beneficial to prolonging the service life of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the X-ray diffraction pattern of copper catalyst A1. DETAILED DESCRIPTION
[0028] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0029] As mentioned above, the first aspect of the present invention provides a copper catalyst, which contains Cu element, Mn element and Al element. Based on the total weight of the copper catalyst, the content of Cu element in the copper catalyst is 32wt%-60wt%, the content of Mn element is 3wt%-16wt%, and the content of Al element is 10wt%-32wt%;
[0030] The copper catalyst contains CuO crystal phase and / or CuAl2O4 spinel phase.
[0031] Preferably, the copper catalyst has a Cu content of 34wt%-56wt%, a Mn content of 3.2wt%-12wt%, and an Al content of 12wt%-30wt%. The inventors of the present invention have found that in this preferred case, the CuO crystal phase and / or CuAl2O4 spinel phase in the obtained copper catalyst has better crystallinity.
[0032] Preferably, the specific surface area of the copper catalyst is 20-100 m 2 / g, pore volume is 0.1-2.0cm 3 The inventors of the present invention have found that in this preferred case, the obtained copper catalyst has better catalytic activity.
[0033] More preferably, the bulk density of the copper catalyst is 1.0-1.5 g / mL.
[0034] Further preferably, the sodium content in the copper catalyst is 500-5000 ppm.
[0035] Specifically, in the present invention, the specific surface area and pore volume of the copper catalyst are measured by Anton Paar's specific surface and pore size analyzer Nova600; the bulk density of the copper catalyst is measured by a tap density tester; and the sodium content is measured by an inductively coupled plasma emission spectrometer.
[0036] As mentioned above, the second aspect of the present invention provides a method for preparing a copper catalyst, the method comprising:
[0037] (1) Under the condition of pH value of 8-9, an aqueous solution containing copper salt, manganese salt and aluminum salt is subjected to a coprecipitation reaction at a temperature not lower than 40° C. to obtain intermediate I;
[0038] (2) subjecting the intermediate I to an aging treatment to obtain an intermediate II;
[0039] (3) calcining the intermediate II to obtain the copper catalyst.
[0040] The conditions are controlled so that the content of Cu element in the copper catalyst is 32wt%-60wt%, the content of Mn element is 3wt%-16wt%, and the content of Al element is 10wt%-32wt%; the copper catalyst contains CuO crystal phase and / or CuAl2O4 spinel phase.
[0041] Wherein, in step (1), the present invention has no particular requirements on the specific type of the alkaline solution for adjusting the pH value of the precipitation reaction process, and the alkaline solution can be selected from at least one of sodium carbonate and sodium hydroxide.
[0042] The copper salt, manganese salt and aluminum salt described in the present invention are soluble metal salts containing copper, manganese and aluminum elements respectively or together.
[0043] Preferably, the copper salt is selected from at least one of copper nitrate, copper sulfate and copper chloride.
[0044] Preferably, the manganese salt is selected from at least one of manganese nitrate, manganese sulfate and manganese chloride.
[0045] Preferably, the aluminum salt is selected from at least one of sodium aluminate, aluminum sulfate and aluminum trichloride.
[0046] Preferably, the coprecipitation reaction conditions include: a temperature of 70-90° C. and a time of 2.5-4 hours. The inventors of the present invention have found that in this preferred case, the CuO crystal phase and / or CuAl2O4 spinel phase in the obtained copper catalyst has better crystallinity.
[0047] According to a specific embodiment, the co-precipitation reaction uses a peristaltic pump to contact and mix the raw materials in a parallel flow manner. The present invention has no special requirements on the dripping rate of each raw material. Those skilled in the art can appropriately adjust the dripping rate of the peristaltic pump according to actual conditions to control the precipitation reaction time to be about 3 hours.
[0048] More preferably, the aging treatment conditions include: a temperature of 25-30° C. and a time of 2-3 hours. The inventors of the present invention have found that under this preferred condition, the obtained copper catalyst has better catalytic activity.
[0049] Further preferably, the conditions of the calcination treatment include: a calcination temperature of 400-600° C. and a calcination time of 5-10 h.
[0050] More preferably, the calcination treatment is performed in an air atmosphere.
[0051] According to a specific embodiment, in step (3), before the intermediate II is calcined, the intermediate II is also washed, filtered and dried, and then ground. The ground powder is mixed with graphite and then sliced into 3x3mm cylindrical particles. The particles obtained above are then calcined to obtain the copper catalyst.
[0052] The present invention has no particular requirement on the particle size of the powder obtained by the grinding. Those skilled in the art can make the ground powder and graphite be mixed and dispersed evenly according to actual needs.
[0053] Preferably, the amount of graphite used is 2-4 parts by weight relative to 100 parts by weight of the ground powder. Particularly preferably, the amount of graphite used is 3 parts by weight relative to 100 parts by weight of the ground powder.
[0054] It should be noted that the precipitation reaction time of the present invention is measured from the time when the copper salt, the manganese salt, the aluminum salt and the alkaline solution begin to mix.
[0055] Preferably, the conditions are controlled so that the content of Cu element in the copper catalyst is 34wt%-56wt%, the content of Mn element is 3.2wt%-12wt%, and the content of Al element is 12wt%-30wt%. The inventors of the present invention have found that in this preferred case, the CuO crystal phase and / or CuAl2O4 spinel phase in the obtained copper catalyst has better crystallinity.
[0056] The specific surface area of the copper catalyst obtained by the preparation method described in the second aspect is 20-100m 2 / g, pore volume is 0.1-2.0cm 3 The inventors of the present invention have found that in this preferred case, the obtained copper catalyst has better catalytic activity.
[0057] Preferably, the bulk density of the copper catalyst is 1.0-1.5 g / mL.
[0058] Preferably, the sodium content in the copper catalyst is 500-5000 ppm.
[0059] As mentioned above, the third aspect of the present invention provides a copper catalyst prepared by the method described in the second aspect.
[0060] As mentioned above, the fourth aspect of the present invention provides the use of the copper catalyst described in the first aspect and / or the third aspect in the dehydrogenation of alcohol compounds to prepare esters and / or ketone compounds.
[0061] Preferably, the alcohol compound is C 2-12 monohydric alcohol or polyhydric alcohol.
[0062] The present invention has no particular limitation on the ester compounds. Depending on the alcohol compounds, the ester compounds obtained by dehydrogenation may be straight-chain esters, cyclic lactones or other ester compounds.
[0063] As mentioned above, the fifth aspect of the present invention provides a method for preparing ester and / or ketone compounds by dehydrogenation of alcohol compounds, the method comprising: dehydrogenating the alcohol compounds in the presence of a copper catalyst to obtain ester and / or ketone compounds;
[0064] The alcohol compound is C 2-12 monohydric alcohol or polyhydric alcohol.
[0065] The copper catalyst is the copper catalyst described in the first aspect and / or the third aspect.
[0066] Preferably, the alcohol compound is selected from at least one of sec-butyl alcohol, 1,4-butanediol, 1,5-pentanediol and 1,6-hexanediol.
[0067] Particularly preferably, the alcohol compound is 1,4-butanediol.
[0068] Preferably, the reaction conditions of the dehydrogenation treatment include: reaction temperature of 160-250°C, reaction pressure of 0.05-1MPa, hydrogen-to-alcohol molar ratio of 0-30, liquid hourly space velocity of alcohol compound of 0.5-3h -1 .
[0069] More preferably, the reaction conditions of the dehydrogenation treatment include: reaction temperature of 170-220°C, reaction pressure of 0.1-0.5 MPa, hydrogen-to-alcohol molar ratio of 1-20, liquid hourly space velocity of alcohol compound of 0.5-2h -1 The inventors of the present invention have found that in this preferred case, in the dehydrogenation reaction of alcohol compounds, the conversion rate of alcohol compounds and the selectivity of product esters and / or ketone compounds are both higher.
[0070] According to a specific implementation, before the obtained catalyst is applied to the reaction, the catalyst is first loaded into a tubular reactor, both ends of the catalyst bed are filled with porcelain balls, and reduced in a hydrogen atmosphere at, for example, 250° C. for, for example, 12 hours.
[0071] It should be noted that in the above method for preparing ester compounds by dehydrogenating alcohol compounds, the hydrogen-to-alcohol molar ratio is the ratio of the molar numbers of hydrogen to the alcohol compound in the reaction system.
[0072] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the instruments, reagents, materials, etc. involved are all conventional instruments, reagents, materials, etc., which can be obtained through regular commercial channels. Among them, unless otherwise specified, the reagents used are all ordinary commercially available analytically pure products.
[0073] Graphite: The average particle diameter is 70-80 μm, purchased from Qingdao Mingrun Chenyue Graphite Co., Ltd.
[0074] Preparation Example 1: The content of the elements in the copper catalyst designed and prepared is Cu: 51.9wt%, Mn: 6.3wt%, Al: 13.2wt%
[0075] Weigh 1616.64 g of copper nitrate solution (the content of Cu element in the copper nitrate solution is 14 wt%) and put it into a beaker, add 179.44 g of manganese nitrate solution (the content of manganese nitrate in the manganese nitrate solution is 50 wt%) to the copper nitrate solution, stir and mix, and record it as solution 1.
[0076] Weigh 473.77 g of sodium aluminate solution (the content of sodium aluminate in the sodium aluminate solution is 37 wt %) and put it into a beaker. Add deionized water to dilute it to 720 mL and stir to mix. This is recorded as Solution 2.
[0077] Weigh 300 g of sodium carbonate and 300 g of sodium hydroxide and dissolve them in 3000 mL of deionized water to prepare a mixed solution with a mass ratio of sodium carbonate to sodium hydroxide of 1:1, which is recorded as Solution 3.
[0078] At 80°C and under continuous stirring, solution 1, solution 2 and solution 3 were added dropwise to a precipitation tank using a peristaltic pump for 3 hours. The pH value was controlled to be 8.5 during the entire precipitation reaction process. The solution was then aged at 25°C for 2 hours. The catalyst was washed and filtered and then dried at 120°C for 12 hours. The mixture was then ground and the powder obtained by grinding was mixed with graphite at a weight ratio of 100:3 and then tableted into 3x3mm cylindrical particles. The particles were then calcined at 500°C in an air atmosphere for 8 hours to obtain copper catalyst A1.
[0079] The composition of the copper catalyst A1 was detected by inductively coupled plasma emission spectrometry, and the results showed that the content of the elements in the copper catalyst A1 was Cu: 51.9wt%, Mn: 6.2wt%, and Al: 13.2wt%.
[0080] Figure 1The X-ray diffraction pattern of the copper catalyst A1 is shown. The XRD characteristic peaks of the copper catalyst A1 correspond to the characteristic peaks of CuO and CuAl2O4. Figure 1 It can be seen that the copper catalyst A1 contains CuO crystal phase and CuAl2O4 spinel phase.
[0081] Preparation Example 2: The content of the elements in the copper catalyst designed and prepared is Cu: 39.9wt%, Mn: 6.3wt%, Al: 21.2wt%
[0082] Weigh 1243.57 g of a copper nitrate solution (the content of Cu element in the copper nitrate solution is 14 wt%) and put it into a beaker, add 179.44 g of a manganese nitrate solution (the content of manganese nitrate in the manganese nitrate solution is 50 wt%) to the copper nitrate solution, stir and mix, and record it as solution 1.
[0083] Weigh 758.03 g of sodium aluminate solution (the content of sodium aluminate in the sodium aluminate solution is 37 wt %) and put it into a beaker. Add deionized water to dilute it to 1150 mL and stir to mix. This is recorded as Solution 2.
[0084] Weigh 300 g of sodium carbonate and 300 g of sodium hydroxide and dissolve them in 3000 mL of deionized water to prepare a mixed solution with a mass ratio of sodium carbonate to sodium hydroxide of 1:1, which is recorded as Solution 3.
[0085] The subsequent operations of this preparation example were carried out in the same manner as in Preparation Example 1. The process parameters of the precipitation reaction, aging and calcination treatment were consistent with those in Preparation Example 1, and copper catalyst A2 was obtained.
[0086] The composition of the copper catalyst A2 was detected by inductively coupled plasma emission spectrometry, and the results showed that the content of the elements in the copper catalyst A2 was Cu: 40wt%, Mn: 6.2wt%, and Al: 21.1wt%.
[0087] The copper catalyst A2 prepared in this preparation example has XRD characteristic diffraction peaks similar to those of the copper catalyst A1, that is, the copper catalyst A2 contains CuO crystal phase and CuAl2O4 spinel phase.
[0088] Preparation Example 3: The content of the elements in the copper catalyst designed and prepared is Cu: 35.9wt%, Mn: 11.4wt%, Al: 19.6wt%
[0089] Weigh 1119.21 g of a copper nitrate solution (the content of Cu element in the copper nitrate solution is 14 wt%) and place it in a beaker, add 322.99 g of a manganese nitrate solution (the content of manganese nitrate in the manganese nitrate solution is 50 wt%) to the copper nitrate solution, stir and mix, and record it as solution 1.
[0090] Weigh 701.18 g of sodium aluminate solution (the content of sodium aluminate in the sodium aluminate solution is 37 wt %) and put it into a beaker. Add deionized water to dilute it to 1070 mL and stir to mix. This is recorded as Solution 2.
[0091] Weigh 300 g of sodium carbonate and 300 g of sodium hydroxide and dissolve them in 3000 mL of deionized water to prepare a mixed solution with a mass ratio of sodium carbonate to sodium hydroxide of 1:1, which is recorded as Solution 3.
[0092] The subsequent operations of this preparation example were carried out in the same manner as in Preparation Example 1. The process parameters of the precipitation reaction, aging and calcination treatment were consistent with those in Preparation Example 1, and copper catalyst A3 was obtained.
[0093] The composition of the copper catalyst A3 was detected by inductively coupled plasma emission spectrometry, and the results showed that the content of the elements in the copper catalyst A3 was Cu: 36wt%, Mn: 11.4wt%, and Al: 19.5wt%.
[0094] The copper catalyst A3 prepared in this preparation example has XRD characteristic diffraction peaks similar to those of the copper catalyst A1, that is, the copper catalyst A3 contains CuO crystal phase and CuAl2O4 spinel phase.
[0095] Preparation Example 4
[0096] A method similar to that of Preparation Example 1 was used, except that the conditions of the precipitation reaction in Preparation Example 1 were adjusted to: temperature 40° C., time 4 h, to obtain copper catalyst A4.
[0097] The composition of the copper catalyst A4 was detected by inductively coupled plasma emission spectrometry, and the results showed that the content of the elements in the copper catalyst A4 was Cu: 51.8wt%, Mn: 6.2wt%, and Al: 13.0wt%.
[0098] The copper catalyst A4 prepared in this preparation example has XRD characteristic diffraction peaks similar to those of the copper catalyst A1, that is, the copper catalyst A4 contains CuO crystal phase and CuAl2O4 spinel phase.
[0099] Preparation Example 5: The content of the elements in the copper catalyst designed and prepared is Cu: 39.9wt%, Mn: 13.3wt%, Al: 15.3wt%
[0100] Weigh 1243.57 g of a copper nitrate solution (the content of Cu element in the copper nitrate solution is 14 wt%) and put it into a beaker, add 376.82 g of a manganese nitrate solution (the content of manganese nitrate in the manganese nitrate solution is 50 wt%) to the copper nitrate solution, stir and mix, and record it as solution 1.
[0101] Weigh 549.57 g of sodium aluminate solution (the content of sodium aluminate in the sodium aluminate solution is 37 wt %) and put it into a beaker. Add deionized water to dilute it to 550 mL and stir to mix. This is recorded as Solution 2.
[0102] Weigh 300 g of sodium carbonate and 300 g of sodium hydroxide and dissolve them in 3000 mL of deionized water to prepare a mixed solution with a mass ratio of sodium carbonate to sodium hydroxide of 1:1, which is recorded as Solution 3.
[0103] The subsequent operations of this preparation example were carried out in the same manner as in Preparation Example 1. The process parameters of the precipitation reaction, aging and calcination treatment were consistent with those in Preparation Example 1, and copper catalyst A5 was obtained.
[0104] The composition of the copper catalyst A5 was detected by inductively coupled plasma emission spectrometry, and the results showed that the content of the elements in the copper catalyst A5 was Cu: 39.9wt%, Mn: 13.2wt%, and Al: 15.1wt%.
[0105] The copper catalyst A5 prepared in this preparation example has XRD characteristic diffraction peaks similar to those of the copper catalyst A1, that is, the copper catalyst A5 contains CuO crystal phase and CuAl2O4 spinel phase.
[0106] Preparation Example 6:
[0107] A method similar to that of Preparation Example 1 was adopted, except that the calcination conditions in Preparation Example 1 were adjusted to: calcination temperature of 500° C. and time of 12 h in air atmosphere, to obtain copper catalyst A6.
[0108] The composition of the copper catalyst A6 was detected by inductively coupled plasma emission spectrometry, and the results showed that the content of the elements in the copper catalyst A6 was Cu: 51.8wt%, Mn: 6.2wt%, and Al: 13.0wt%.
[0109] The copper catalyst A6 prepared in this preparation example has XRD characteristic diffraction peaks similar to those of the copper catalyst A1, that is, the copper catalyst A6 contains CuO crystal phase and CuAl2O4 spinel phase.
[0110] Comparative Preparation Example 1: The content of the elements in the designed copper catalyst is Cu: 30.4wt%, Mn: 1.9wt%, Al: 31.2wt%
[0111] Weigh 945.11 g of a copper nitrate solution (the content of Cu element in the copper nitrate solution is 14 wt%) and put it into a beaker, add 53.83 g of a manganese nitrate solution (the content of manganese nitrate in the manganese nitrate solution is 50 wt%) to the copper nitrate solution, stir and mix, and record it as Solution 1.
[0112] Weigh 1118.09 g of sodium aluminate solution (the content of sodium aluminate in the sodium aluminate solution is 37 wt %) and put it into a beaker. Add deionized water to dilute it to 1700 mL and stir to mix. This is recorded as Solution 2.
[0113] Weigh 300 g of sodium carbonate and 300 g of sodium hydroxide and dissolve them in 3000 mL of deionized water to prepare a mixed solution with a mass ratio of sodium carbonate to sodium hydroxide of 1:1, which is recorded as Solution 3.
[0114] The subsequent operations of this preparation example were carried out in the same manner as in Preparation Example 1. The process parameters of the precipitation reaction, aging and calcination treatment were consistent with those in Preparation Example 1, and copper catalyst D-A1 was obtained.
[0115] The composition of the copper catalyst D-A1 was detected by inductively coupled plasma emission spectrometry, and the results showed that the content of elements in the copper catalyst D-A1 was Cu: 30.4wt%, Mn: 1.9wt%, and Al: 31.1wt%.
[0116] Comparative Preparation Example 2
[0117] The designed copper catalyst contains 51.9 wt% Cu, 6.3 wt% Zn and 14.1 wt% Al.
[0118] 1616.64 g of a copper nitrate solution (the content of Cu element in the copper nitrate solution is 14 wt%) was weighed and placed in a beaker, 133.82 g of zinc nitrate hexahydrate was added to the copper nitrate solution, and the mixture was stirred and mixed, and the mixture was recorded as Solution 1.
[0119] Weigh 504.09 g of sodium aluminate solution (the content of sodium aluminate in the sodium aluminate solution is 37 wt %) and put it into a beaker. Add deionized water to dilute it to 766 mL and stir to mix. This is recorded as Solution 2.
[0120] Weigh 300 g of sodium carbonate and 300 g of sodium hydroxide and dissolve them in 3000 mL of deionized water to prepare a mixed solution with a mass ratio of 1:1, which is recorded as Solution 3.
[0121] The subsequent operations of this preparation example were carried out in the same manner as in Preparation Example A1. The process parameters of the precipitation reaction, aging and calcination treatment were consistent with those in Preparation Example 1, and copper catalyst D-A2 was obtained.
[0122] The composition of the copper catalyst D-A2 was detected by inductively coupled plasma emission spectrometry, and the results showed that the content of elements in the copper catalyst D-A2 was Cu: 52wt%, Zn: 6.3wt%, and Al: 14wt%.
[0123] For the copper catalysts obtained in all the above preparation examples, their specific surface area and pore volume were measured using Anton Paar's specific surface and pore size analyzer Nova600, their bulk density was measured using a tap density tester, and their sodium content was measured using an inductively coupled plasma emission spectrometer. The specific results are shown in Table 1.
[0124] Table 1
[0125]
[0126] Example 1
[0127] S1: 13 ml of copper catalyst A1 was loaded into a tubular reactor with an inner diameter of 10 mm, both ends of the catalyst bed were filled with porcelain balls, and reduced under pure hydrogen at 250°C for 12 h.
[0128] S2: 1,4-butanediol was used as the raw material, the reaction temperature was 200°C, the reaction pressure was 0.1 MPa, the hydrogen-alcohol molar ratio was 15, and the liquid hourly space velocity of 1,4-butanediol was 1h -1 The reaction is carried out under the conditions of to obtain the product γ-butyrolactone.
[0129] Embodiment 2-6
[0130] The same process conditions as in Example 1 were used, except that:
[0131] In Example 2, the copper catalyst A2 of the same volume is used to replace the copper catalyst A1 in Example 1;
[0132] In Example 3, the copper catalyst A3 of the same volume is used to replace the copper catalyst A1 in Example 1;
[0133] In Example 4, the copper catalyst A4 of the same volume was used to replace the copper catalyst A1 in Example 1;
[0134] In Example 5, the copper catalyst A5 of the same volume is used to replace the copper catalyst A1 in Example 1;
[0135] In Example 6, the copper catalyst A6 of the same volume was used to replace the copper catalyst A1 in Example 1.
[0136] Example 7
[0137] The same process conditions as in Example 1 were used, except that:
[0138] In step S2, the raw material used is 1,5-pentanediol, and the rest is the same as in Example 1.
[0139] Example 8
[0140] The same process conditions as in Example 1 were used, except that:
[0141] In step S2, the reaction conditions are: reaction temperature of 250°C, reaction pressure of 0.05 MPa, hydrogen-to-alcohol molar ratio of 30, liquid hourly space velocity of 1,4-butanediol of 0.4 h -1 , the rest are the same as in Example 1.
[0142] Comparative Example 1
[0143] The same process conditions as in Example 1 were used, except that:
[0144] In Comparative Example 1, the copper catalyst A1 in Example 1 was replaced with the same volume of copper catalyst D-A1.
[0145] Comparative Example 2: The same process conditions as Example 1 were used, except that:
[0146] In Comparative Example 2, the copper catalyst A1 in Example 1 was replaced with the same volume of copper catalyst D-A2.
[0147] The dehydrogenation products obtained in all the above Examples 1 to 8 and Comparative Examples 1 to 2 were analyzed using a gas chromatograph area normalization method, and the results are shown in Table 2.
[0148] The calculation formulas for the reactant conversion and target product selectivity in Table 2 are:
[0149] Reactant conversion rate % = [(amount of reactant before reaction - amount of reactant after equilibrium) / amount of reactant before reaction] × 100%
[0150] Selectivity of target product % = [amount of target product / (amount of reactant before reaction - amount of reactant after equilibrium)] × 100%
[0151] Table 2
[0152] Reactant conversion rate / % Selectivity of target product / % Example 1 99.9 99.9 Example 2 99.6 99.7 Example 3 99.5 99.6 Example 4 99.3 99.5 Example 5 99.1 99.4 Example 6 99.0 99.0 Example 7 99.0 99.1 Example 8 99.1 98.2 Comparative Example 1 95.4 94.7 Comparative Example 2 98.2 98.0
[0153] It can be seen from the results in Table 2 that the copper catalyst prepared by the present invention has the advantages of high raw material conversion rate and high target product selectivity when applied to the dehydrogenation of alcohol compounds to prepare ester compounds and / or ketone compounds. Furthermore, in combination with all the specific embodiments, it can be concluded that the copper catalyst prepared by the present invention still has good catalytic activity under the conditions of low temperature, low hydrogen-to-alcohol ratio and high space velocity in the dehydrogenation reaction.
[0154] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A copper catalyst, characterized in that The copper catalyst contains Cu, Mn and Al elements. Based on the total weight of the copper catalyst, the content of Cu in the copper catalyst is 32wt%-60wt%, the content of Mn in the copper catalyst is 3wt%-16wt%, and the content of Al in the copper catalyst is 10wt%-32wt%. The copper catalyst contains CuO crystal phase and / or CuAl2O4 spinel phase.
2. The copper catalyst according to claim 1, wherein The copper catalyst has a Cu content of 34wt%-56wt%, a Mn content of 3.2wt%-12wt%, and an Al content of 12wt%-30wt%.
3. The copper catalyst according to claim 1 or 2, wherein The specific surface area of the copper catalyst is 20-100m 2 / g, pore volume is 0.1-2cm 3 / g; Preferably, the bulk density of the copper catalyst is 1-1.5 g / mL; Preferably, the sodium content in the copper catalyst is 500-5000 ppm.
4. A method for preparing a copper catalyst, characterized in that: The method includes: (1) Under the condition of pH 8-9, an aqueous solution containing copper salt, manganese salt and aluminum salt is subjected to a coprecipitation reaction at a temperature not lower than 40° C. to obtain an intermediate I; (2) subjecting the intermediate I to an aging treatment to obtain an intermediate II; (3) calcining the intermediate II to obtain the copper catalyst; The conditions are controlled so that the content of Cu element in the copper catalyst is 32wt%-60wt%, the content of Mn element is 3wt%-16wt%, and the content of Al element is 10wt%-32wt%; the copper catalyst contains CuO crystal phase and / or CuAl2O4 spinel phase.
5. The preparation method according to claim 4, wherein The coprecipitation reaction conditions include: temperature of 70-90°C and time of 2.5-4h; Preferably, the aging treatment conditions include: temperature of 25-30°C and time of 2-3h; Preferably, the conditions of the calcination treatment include: a calcination temperature of 400-600° C. and a calcination time of 5-10 h.
6. The preparation method according to claim 4 or 5, wherein: The conditions are controlled so that the content of Cu element in the copper catalyst is 34wt%-56wt%, the content of Mn element is 3.2wt%-12wt%, and the content of Al element is 12wt%-30wt%.
7. The preparation method according to any one of claims 4 to 6, wherein: The specific surface area of the copper catalyst is 20-100m 2 / g, pore volume is 0.1-2cm 3 / g; Preferably, the bulk density of the copper catalyst is 1.0-1.5 g / mL; Preferably, the sodium content in the copper catalyst is 500-5000 ppm.
8. A copper catalyst prepared by the preparation method according to any one of claims 4 to 7.
9. Use of the copper catalyst according to any one of claims 1 to 3 and 8 in the dehydrogenation of alcohol compounds to prepare esters and / or ketone compounds; Preferably, the alcohol compound is C 2-12 monohydric alcohol or polyhydric alcohol.
10. A method for preparing esters and / or ketone compounds by dehydrogenation of alcohol compounds, characterized in that: The method comprises: dehydrogenating an alcohol compound in the presence of a copper catalyst to obtain an ester and / or ketone compound; The alcohol compound is C 2-12 Monohydric alcohol or polyhydric alcohol; The copper catalyst is the copper catalyst described in any one of claims 1-3 and 8.
11. The method according to claim 10, wherein: The alcohol compound is selected from at least one of sec-butyl alcohol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol; Preferably, the alcohol compound is 1,4-butanediol.
12. The method according to claim 10 or 11, wherein: The reaction conditions of the dehydrogenation treatment include: reaction temperature of 160-250°C, reaction pressure of 0.05-1MPa, hydrogen-to-alcohol molar ratio of 0-30, liquid hourly space velocity of alcohol compound of 0.5-6h -1 .
Citation Information
Patent Citations
Process for producing high-stability central-hole material Cu-Zn-Al2O3, and application of the same in producing mellow wine dehydrogenating catalyst
CN101269331A
Catalyst for preparing cyclohexanone by cyclohexanol dehydrogenation
CN101757922A
Production method of gamma-butyrolactone
CN103044367A
Delta-valerolactone production method
CN103980241A